Tensioregulome as an accompaniment of quantitative-qualitative blood pressure clusters - Popovych, Igor; Kozyavkina, Nataliya; Vovchyna, Yuliya; Voronych-Semchenko, Nataliya; Zukow, Walery; Popovych, Dariya (Journal of Education, Health and Sport, 2022)
Background. Earlier we studied the neural, endocrine, immune, microbiome and metabolome accompaniments of quantitative-qualitative blood pressure (BP) clusters of profile patients of Truskavets’ spa. The obtained results give us grounds to put forward the concept of tensioregulome by analogy with the metabolome and the microbiome. The purpose of this study is detailing this concept. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP. We determined parameters of EEG and HRV, plasma levels of adaptation hormones, electrolytes, lipids, and nitrogenous metabolites, components of humoral, cellular, and phagocytic links of immunity and markers of pyelonephritis. Results. The forward stepwise program identified 26 tensioregulome parameters as characteristic of quantitative-qualitative blood pressure clusters: 10 EEG, 6 metabolic, 6 immune, testosterone, cotrisol, sympathetic tone as well as sex. The accuracy of patient classification is 98,9%. Another 25 parameters were found to be characteristic, but were outside the discriminant model, including 11 EEG, 2 HRV, 5 metabolic, 4 immune, bacteriuria, body mass index, and age. Both linear and non-linear correlations between the BP and tensioregulome parameters were revealed. Conclusion. The quantitative-qualitative blood pressure clusters have a characteristic accompaniment named tensioregulome.